Prevalence and severity of molar-incisor hypomineralization, is there an association with socioeconomic status? A cross-sectional study in Chilean schoolchildren - Harz, D.; Catalán Gamonal, B.; Matute García, S.; Jeremias, F. [UNESP]; Martin, J.; Fresno, M. C. (Springer Nature, 2023)
Purpose: Data about molar-incisor hypomineralization (MIH) prevalence and its severity remains limited for some Latin American countries. Furthermore, its association with socioeconomic status (SES) is still unclear. Thus, this study aims to determine the prevalence and severity of MIH in Santiago, Chile and explore its association with SES. Methods: A cross-sectional study with schoolchildren between 6 and 12 years was conducted. Children were evaluated using the European Academy of Paediatric Dentistry to diagnose MIH, and the Mathu-Muju and Wright criteria to determine its severity. Results: A total of 1,270 children were included. The MIH prevalence was 12.8% without association with gender (p = 0.609). Prevalence was higher among schoolchildren ages 8 and 9 (p = 0.002), and in lower SES (p = 0.007). MIH mild cases were the most prevalent (63%), and severity was not related to gender (p = 0.656), age (p = 0.060), or SES (p = 0.174). Conclusions: The prevalence of MIH in the province of Santiago, Chile is 12.8% and was found to have a higher incidence in 8–9-year-old students and among those categorized by low SES. Furthermore, MIH prevalence was associated with low SES. Implications: Public health policies to address MIH in Chile should start with schoolchildren aged 8 to 9, and with low SES.
Keywords: MIH; Molar incisor hypomineralisation; Molar incisor hypomineralization; Prevalence; Severity; Socioeconomic status